Paclobutrazol e etileno na produção de abacaxizeiro ornamental em vaso - Téllez, Hayver Olaya (2020)
The production of ornamental pineapple in a pot requires technical and scientific information to enable its commercialization. In this sense, two experiments were carried out. In the first, it was carried out in a greenhouse, in the experimental area of Embrapa Tropical agroindustry, Fortaleza, CE, the effects of the presence and absence of paclobutrazol (PBZ) and of periods of floral induction on the production of the ornamental pineapple, hybrid 'D', in pot. The experimental design was a randomized block, factorial arrangement (2 x 5) + 1, with four repetitions. The primary treatments were the presence and absence of PBZ. The secondary treatments were five moments of floral induction with ethylene. The additional treatment was the absence of PBZ and ethylene (Ethrel®). Before each application of ethylene, at 90, 120, 150, 180 and 210 days after the transplantation (DAT), vegetative growth was evaluated and, six days after, at 96, 126, 156, 186 and 216 DAT, gas exchange . Forty days after ethylene application, at 130, 160, 190, 220 and 250 DAT, the leaf area, the accumulation of fresh and dry mass, macro and micronutrients plus sodium were evaluated. At the end of the experiment, at 255 DAT, the vegetative growth, flowering and aesthetic quality of the plants were evaluated. PBZ affected plant size, decreasing size, leaf area, mass accumulation and macro and micronutrients plus sodium. Ethylene did not affect gas exchange. Potassium and manganese are the most required macro and micronutrient. The plants, at 255 DAT, did not respond to floral induction with ethylene, the PBZ reduced the size of the plants until their ornamental use. In the second experiment, carried out in the experimental area of the Agrometeorological Station, located at the Federal University of Ceará, Fortaleza, CE, the effects of PBZ on the size and growth of seedlings of ornamental pineapple plants were evaluated. The experimental design was a randomized block, an arrangement of subdivided plots (3 x 4), with eight repetitions. The primary treatments were three types of seedlings: sucker and arial sucker from plants treated with PBZ and arial sucker from plants not treated with PBZ. The secondary treatments were four evaluation periods: 0; 30; 60 and 90 days after planting (DAP). The vegetative size and growth over time and the growth rate at 90 DAP were evaluated. The seedlings of plants treated with PBZ showed smaller size and vegetative growth and a higher growth rate. The effect of PBZ decreased after 60 DAP.